Mathematical computation of water quality index to determine surface water quality of manyad storage tank, Aurangabad district, Maharashtra, India - L. Dhumal, M. (International Journal of Physical Research, 2021)
The present work aims to assess the water quality index (WQI) of Manyad Storage tank, of Aurangabad district, Maharashtra, India. The surface water sample were assessed for physico-chemical parameters namely pH, Electrical Conductivity, Total Dissolved Solid, Total Hardness, Bicarbonate, Chlorides, Sulphates, Nitrates, Calcium, Magnesium, Sodium, Potassium and Fluoride in post-monsoon season of 2020. For calculating the water quality index (WQI), thirteen parameters namely, pH, electrical conductivity, total dissolved solids, total hardness, bicarbonate, calcium, magnesium, sodium, potassium, chloride, sulphate, nitrate and fluorides were considered. Weighted arithmetic water quality index method was used to find surface water quality index (WQI). The water quality index of surface water found to be 96.24 indicating poor water category, which shows that whole water from the Manyad Storage tank is of very poor quality and treatment must be given before use for drinking purpose.Â Â